2018
DOI: 10.17159/2519-0105/2018/v73no8a4
|View full text |Cite
|
Sign up to set email alerts
|

Root canal treatment in mandibular canines with two roots: a review of the literature and a report of three cases

Abstract: Endodontic treatment may sometimes fail because the morphological features of the tooth can adversely affect the treatment procedures. Mandibular canines can present with complex internal anatomy and many investigators have reported associated anatomical variations. This paper describes three clinical case reports of mandibular canines, each with two roots and two canals. In addition, the prevalence, aetiology, root morphology and the clinical and radiographic diagnoses for mandibular canines that present with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…International studies reported 5 -15% of mandibular canines to have two canals [9-11, 13, 20]. Different root canal configurations were reported in Saudi population [5,[14][15][16]. Recently, Aldahman et al performed a CBCT anatomical assessment of mandibular canines in Saudi population.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…International studies reported 5 -15% of mandibular canines to have two canals [9-11, 13, 20]. Different root canal configurations were reported in Saudi population [5,[14][15][16]. Recently, Aldahman et al performed a CBCT anatomical assessment of mandibular canines in Saudi population.…”
Section: Discussionmentioning
confidence: 99%
“…Only one published study reported the incidence of 2 canals in Saudi population (Al-Dahman et al). Few Case reports were found in the literature about clinical cases with 2 canals [5,[14][15][16]. In the current report, a clinical case was presented about successful endodontic management of mandibular canine with 2 canals in Saudi female, in order to add to the current knowledge about root canal morphology in Saudi population.…”
Section: Introductionmentioning
confidence: 98%